2001
DOI: 10.1023/a:1008995217664
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Obesity is associated with more forms of cancer than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
113
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(123 citation statements)
references
References 63 publications
5
113
0
Order By: Relevance
“…These results should be considered with caution, however, as some of these studies found no statistically significant increase in liver cancer risk and no trend of increasing risk with increasing BMI (Rapp et al, 2005), did not control accurately for all major risk factors for HCC (Moller et al, 1994) or controlled only for hospital discharge of alcoholism and diabetes (Calle et al, 2003;Samanic et al, 2004), or found no increased risk for liver cancer due to obesity when excluding patients with diabetes (Wolk et al, 2001). By contrast, in a large USA cohort study of male veterans hospitalized with a diagnosis of obesity, excess risks for liver cancer were also observed when the analysis was restricted to white men without a history of diabetes or alcoholism (Samanic et al, 2004).…”
Section: Diabetes and Hepatocellular Carcinomamentioning
confidence: 84%
See 1 more Smart Citation
“…These results should be considered with caution, however, as some of these studies found no statistically significant increase in liver cancer risk and no trend of increasing risk with increasing BMI (Rapp et al, 2005), did not control accurately for all major risk factors for HCC (Moller et al, 1994) or controlled only for hospital discharge of alcoholism and diabetes (Calle et al, 2003;Samanic et al, 2004), or found no increased risk for liver cancer due to obesity when excluding patients with diabetes (Wolk et al, 2001). By contrast, in a large USA cohort study of male veterans hospitalized with a diagnosis of obesity, excess risks for liver cancer were also observed when the analysis was restricted to white men without a history of diabetes or alcoholism (Samanic et al, 2004).…”
Section: Diabetes and Hepatocellular Carcinomamentioning
confidence: 84%
“…Obesity and hepatocellular carcinoma Some population-based cohort studies from Central and Northern Europe and from the USA found that obesity is associated with a 2-4-fold increased risk of liver cancer, higher among men than women (Moller et al, 1994;Wolk et al, 2001;Calle et al, 2003;Samanic et al, 2004;Rapp et al, 2005). These results should be considered with caution, however, as some of these studies found no statistically significant increase in liver cancer risk and no trend of increasing risk with increasing BMI (Rapp et al, 2005), did not control accurately for all major risk factors for HCC (Moller et al, 1994) or controlled only for hospital discharge of alcoholism and diabetes (Calle et al, 2003;Samanic et al, 2004), or found no increased risk for liver cancer due to obesity when excluding patients with diabetes (Wolk et al, 2001).…”
Section: Diabetes and Hepatocellular Carcinomamentioning
confidence: 99%
“…Positive associations with ovarian cancer and body mass have been in the range of 1.5-2.0 for the highest categories studied (Cramer et al, 1884;Lew and Garfinkel, 1979;Farrow et al, 1989;Purdie et al, 2001;Calle et al, 2003), although several studies have not shown an association (Slattery et al, 1989;Moller et al, 1994;Mink et al, 1995;Wolk et al, 2001).…”
Section: Other Cancersmentioning
confidence: 97%
“…Available studies have consistently found elevated risks for women (of about twofold), but generally have had too few cases to evaluate the association in men (Lew and Garfinkel, 1979;Moller et al, 1994;Strom et al, 1995;Zatonski et al, 1997;Wolk et al, 2001;Calle et al, 2003). Obesity is thought to operate indirectly to increase the risk of gallbladder cancer by increasing the risk of gallstones, which, in turn, causes chronic inflammation and increased risk of biliary tract cancer (World Cancer Research Fund and American Institute for Cancer Research, 1997).…”
Section: Other Cancersmentioning
confidence: 99%
“…Low levels of adiponectin have been found in a number of obesity related cancers as well as cancers associated with insulin resistance [4] such as breast [5][6][7], prostate [8] and colon [9]. It has been suggested that reduced levels of adiponectin lead to the development of insulin resistance and compensatory chronic hyperinuslinemia which in turn lead to reduced liver synthesis of IGFBP1 and IGFBP2.…”
Section: Introductionmentioning
confidence: 99%